THE EFFECT OF USING SKIMMING AND SCANNING ON THE STUDENTS’ ABILITY IN READING COMPREHENSION AT GRADE X IN SMA KAMPUS NOMMENSEN PEMATANGSIANTAR - Siahaan, Desta Gloria; Pangaribuan, Marnala (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2022)
This study attempted to find out the effect of using skimming and scanning to the students’ ability in reading comprehension at grade X in SMA Kampus Nommensen Pematangsiantar. This research design of is quantitative descriptive. The population of this research is students of SMA Kampus Nommensen Pematangsiantar with cluster sampling data. The researcher gets 60 students as the sample which divided by 30 students as the sample of control class (X-1) and 30 students as the experimental class (X-2). The multiple-choices test is used by the researcher as the instruments to get the data. The test is given to measure the students’ ability in reading comprehension of narrative texts especially in the type of myths. After collected the data, the researcher analyzed the data to find out the effect of skimming and scanning from the calculation scores of pre-test and post-test. Based on the data analysis it is found that the tobserve is higher than ttable (4,54>1,67). So, it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. In other word, it can be stated that Skimming and Scanning significantly affect the students’ reading comprehension at grade X of SMA Kampus Nommensen Pematangsiar.